LINGUOPRAGMATIC FEATURES OF PHRASEOLOGICAL UNITS IN ESL CLASS - Abdullaeva, Dildora (Журнал иностранных языков и лингвистики, 2021)
The article studies pragmatics as a sub-direction of linguistics, and its features as opposition to the intended meaning, relative distance both social and physical. The main purpose of the article is to define and explain the meaning of this term, and why we need it. The research explored comparative method in both finding the theory and suitable examples. The findings of the research show the impact of pragmatics in real life conversation. While socializing people really need pragmatic meaning for understanding speaker’s attitude, feeling and thoughts. Theoretical contributions and practical implications are presented by phraseological units, ideoms and sample authentic dialogues, opposite meaning of semantics argued as pragmatics.